1986
DOI: 10.1111/j.1365-3024.1986.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni: liver phase challenge attrition is a stage‐dependent phenomenon in guinea‐pigs vaccinated with highly irradiated cercariae

Abstract: Guinea-pigs vaccinated with highly irradiated cercariae of Schistosoma mansoni have been examined for their ability to kill challenge parasites at the level of the liver. Skin and lung phase attrition were eliminated by surgical introduction of 4/5 day old schistosomula, or 2, 3 or 6 week schistosomes into the mesenteric vasculature of vaccinated and naive animals. These experiments showed consistently that lung schistosomula and 2 week old parasites were killed preferentially by sensitized animals, but that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The development of CI found in mice could be due to the following reasons: first, the inhibition of egg production eliminate the excretion of soluble egg antigens (SEA) and, hence, the production of blocking antibodies as shown previously in NM mice [31] which may explain the enhancement of CI. Second, comparing with the irradiated vaccine model, established by McLaren and Rogers, the protection against reinfection due to concomitant immunity is dependent on the living adult worms in NM mice [32]. This is supported by [33] who concluded that adult worms might promote anti-larval immunity via the release of antigens, thus creating a barrier against continuous infection and limiting burden size within the host.…”
Section: Discussionmentioning
confidence: 95%
“…The development of CI found in mice could be due to the following reasons: first, the inhibition of egg production eliminate the excretion of soluble egg antigens (SEA) and, hence, the production of blocking antibodies as shown previously in NM mice [31] which may explain the enhancement of CI. Second, comparing with the irradiated vaccine model, established by McLaren and Rogers, the protection against reinfection due to concomitant immunity is dependent on the living adult worms in NM mice [32]. This is supported by [33] who concluded that adult worms might promote anti-larval immunity via the release of antigens, thus creating a barrier against continuous infection and limiting burden size within the host.…”
Section: Discussionmentioning
confidence: 95%
“…Though the order in which cells die in nematodes is invariable, changes in the timing of induction of parasite PCD may promote protection in a number of ways, including the early senesence of the worm, inappropriate development (effects on fecundity), development in abnormal locations or inadequate growth (stunting). This view is supported by the regulatory effects of TNF on schistosomes where 'internal damage in the absence of effects on the worm surface' or 'inhibition of some physiological function' have been reported (Pearce & James 1986, James et al 1990, McLaren & Rogers 1986. Thus the widely reported biochemical and ultrastructural changes induced by protective immune responses in a number of helminths (Haque, et al 1981, Pearce & James 1986, McLaren & Rogers 1986, James et al 1990) may be a consequence of PCD.…”
Section: Introductionmentioning
confidence: 93%
“…Second, comparing with the irradiated vaccine model, established by McLaren et al (24), the protection against reinfection due to concomitant immunity is dependent on the living adult worms in NM mice. This is supported by Brown et al (25), who concluded that adult worms might promote anti-larval immunity via the release of antigens, thus creating a barrier against continuous infection and limiting burden size within the host.…”
Section: Discussionmentioning
confidence: 99%